Controlled synthesis of porous anhydrous cobalt oxalate nanorods with high reversible capacity and excellent cycling stability. (10th July 2015) - Xu, Junmin; He, Lei; Liu, Hui; Han, Tao; Wang, Yongjian; Zhang, Changjin; Zhang, Yuheng
Graphical abstract: Abstract: One-dimensional porous anhydrous cobalt oxalate nanorods are prepared via a facile water-controlled coprecipitate method followed by thermal annealing treatment under N2 at 300 °C. The nanorods are characterized by using X-ray diffraction, scanning electron microscopy and transmission electron microscopy. When evaluated as an anode material for lithium ion batteries, the nanorods exhibit high reversible specific capacity and excellent cycling stability (924 mA h g −1 at 50 mA g −1 after 100 cycles and 709 mA h g −1 at 200 mA g −1 after 220 cycles). This remarkable electrochemical performance is attributed to the one-dimensional porous nanostructure that can provide large electrode/electrolyte contact area and short lithium-ion diffusion pathway, meanwhile reduce the volume expansion during the repeated discharge/charge process.